PEMIKIRAN KHOMEINI TENTANG PENDIDIKAN AKHLAK (SEBUAH KAJIAN ONTOLOGI DAN EPISTIMOLOGI - Khoirul Anwar (Fakultas Agama Islam, 2011)
PEMIKIRAN KHOMEINI TENTANG PENDIDIKAN AKHLAK(SEBUAH KAJIAN ONTOLOGI DAN EPISTIMOLOGI)Oleh :Khoirul Anwar *)ABSTRACTThe phenomenon of anomaly attitude was occurred in adolescent, especially students make manypeople argues that to revive the character education is important. It is presumed, that the anomalyattitude of student relate with ineffectively of character education in school and family. Therefore,the studies of character education from ontology and epistemology viewpoint are needed. Thispaper presents education character according to Khomeini’s concepts. As it was known thatKhomeini was Iran revolution father, he was not a pedagogue, however, he wrote articles whichdiscussed about character education with philosophy and irfan approaches; both was elaboratedsince he still was young. So, it will be interesting to discuss it as a contribution to educationthinking.